Metode Keluarga Yang Belum Memiliki Keturunan Dalam Menjaga Keharmonisan Dari Perspektif Sosiologi Keluarga - Adinda Yuliana; Fandu Dyangga Pradeta (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
Harmony in a household is the dream of every married couple. Building a harmonious family relationship means the establishment of a romantic relationship between married couples in a family and includes everything that has a relationship in the welfare and tranquility of a family. Even though the family does not have an offspring. The research was conducted in Tlogo Village, Kanigoro District, Blitar Regency. With informants 5 families who have no offspring, after approximately 10 households. The research method used in this research is qualitative with a phenomenological approach. The research methods used are observation, documentation and interviews. The results of this study show that the 5 families have good household conditions, despite not having a child. The method used by the 5 families in maintaining harmony in the household is by worshiping together, spending time, commitment, appreciation and affection, conducting medical and non-medical treatment and adoption.